ILLUSTRATIONS TO AID IN EXPLAINING THE TWO METHODS OF PRICING INVENTORY ACTIVITY. - Funk, Roland W. (The Accounting Review, 1950)
The "cost of goods available for sale" is generally understood to consist of (1) the costs incurred in acquiring goods in the current period plus (2) any acquisition costs deferred from preceding periods. The allocation of such acquisition cost to cost-of-goods-sold and ending inventory may be accomplished by several methods, including the "retail" method and the "gross profit" method. The similarities and dissimilarities of these two methods seem to have been neglected or overlooked in accounting textbooks. It may be observed that both of these methods are similar in that they reduce the sales price related to a group of units by an amount of estimated gross margin, with the resulting figure in each case being used as the basis for making an allocation of the cost of goods available. But the two methods differ in that "gross profit" method starts by reducing selling price of units sold, while the retail method begins by reducing the selling price of unsold units. The article presents illustrations to aid in explaining these two methods of pricing inventory activity.